STAFF AND STUDENT RACIAL MICROAGGRESSIONS IN BROWN BRITAIN - Kay, Kavyta (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2021)
There has long been a refusal to regard race as a legitimate category of analysis in higher education, whether from a scholarship or policy perspective. The recognition of the role that universities have played in (re)producing racial injustice is one that is being gradually taken up by scholars who challenge this ignorance by drawing attention to racialised cultures and practices. As a British Asian early career researcher who has found herself at various points in her working life at these charged junctures, it is my firm and absolute belief that these conversations are overdue. Though higher education (HE) is generally regarded as a liberal and progressive space, I offer a counter-narrative in locating myself in this environment in which racial microaggressions (Pierce, 1970) are the norm in order to "keep those at the racial margins in their place" (Pérez Huber & Solórzano, 2015). This article seeks to briefly illustrate some of the ways in which race is experienced through working in HEI with a specific focus on South Asian descent academics. There is a limited understanding of the diversity of British Asians as an ethnic category which is often conflated with an even further limited understanding of Muslimness. This manifests not only in HEI but in the cultural industries and the shaping of the British curriculum, both key sites of knowledge production which circulate discourses about ‘the other’ and in which South Asian communities are either stereotyped or silenced.